New Complexity Analysis of the Path Following Method for Linear Complementarity Problem - Djeffal, El-Amir; Djeffal, Lakhdar; Benoumelaz, Farouk (Intelligent Mathematics II: Applied Mathematics and Approximation Theory, 2016)
In this paper, we present an interior point algorithm for solving an optimization problem using the central path method. By an equivalent reformulation of the central path, we obtain a new search direction which targets at a small neighborhood of the central path. For a full-Newton step interior-point algorithm based on this search direction, the complexity bound of the algorithm is the best known for linear complementarity problem. For its numerical tests some strategies are used and indicate that the algorithm is efficient.